Strategi Komunikasi DPMPD Prov. Kaltim dalam Mendorong Partisipasi Masyarakat melalui Program Pembangunan Desa Berbasis BUMDes - Muhammad Hilmy Sahna Putra; Rina Juwita; Ziya Ibrizah (Institut Nalanda, 2026)
This study analyzes the participatory communication strategy implemented by the Department of Community and Village Empowerment (DPMPD) of East Kalimantan Province in developing Village-Owned Enterprises (BUMDes). The study is motivated by the communication challenges faced in empowering BUMDes, particularly the dominance of top-down communication patterns, unequal dissemination of information, and limited community participation in village economic development. This research aims to identify the communication strategies used by DPMPD, examine the obstacles encountered in their implementation, and analyze the participatory communication approach applied in the empowerment process. This research employed a descriptive qualitative method with a case study approach. Data were collected through interviews, observations, and documentation involving DPMPD officials and several active and inactive BUMDes managers in East Kalimantan. The findings show that DPMPD applies communication strategies through audience identification, message development, method selection, and media utilization. Face-to-face communication, training programs, digital platforms, and collaborative partnerships were used to increase the capacity and participation of BUMDes managers. However, challenges such as limited human resources, geographical barriers, and unequal digital access still hinder the effectiveness of communication. The study concludes that participatory and dialogical communication approaches are essential in strengthening village economic independence and increasing community involvement in sustainable BUMDes development.